Nutrition and allergic diseases in urban and rural communities from the South African Food Allergy cohort. Issue 5 (2nd June 2019) - Botha, Maresa; Basera, Wisdom; Facey‐Thomas, Heidi E.; Gaunt, Ben; Genuneit, Jon; Gray, Claudia L.; Kiragu, Wanjiku; Ramjith, Jordache; Watkins, Alexandra; Levin, Michael E.
Abstract: This study describes and compares allergic diseases and sensitization in urban and rural children in the SAFFA study cohort as well as infant feeding patterns and nutritional status. We assessed the relationship between nutritional status, breastfeeding, complementary feeding patterns, and atopic diseases including aeroallergen and food allergen sensitization, self‐reported atopic dermatitis, allergic rhinitis, asthma, and challenge‐proven food allergy (FA). Methodology: A total of 1185 urban and 398 rural toddlers aged 12‐36 months were screened for food sensitization (FS) and FA using skin prick testing and oral food challenges. Of these, 535 and 347, respectively, were additionally screened for aeroallergen sensitization. Information was collected on infant feeding practices, and anthropometric measurements and clinical signs for atopy were documented. Results: Markedly higher rates of allergy (asthma 9.0% vs 1.0%, eczema 25.6% vs 2.0%, rhinitis 25.3% vs 3.3%, and FA 2.5% vs 0.5%) exist in urban vs rural children. 13.1% unselected urban South African children were sensitized to aeroallergens compared to 3.8% of their rural counterparts and 9.0% to any food compared to 0.5%. Exclusive breastfeeding duration was longer, and there was a later introduction of allergenic foods in rural communities. Obesity rates were similar between the two groups, but rural children were more likely to be stunted. Being overweight was associated with asthma in urban but not rural settings. In the urban cohort, children with FS and allergy were thinner than their peers. Conclusion: Allergy and sensitization rates are significantly higher in unselected urban South African toddlers than their rural counterparts. Risk and protective factors for allergy and atopy may differ between urban and rural settings. Abstract :